Design and evaluation of a gastroretentive drug delivery system for metformin HCl using synthetic and semi-synthetic polymers. - Venkata, Meka; Adinarayana, Gorajana; Senthil, Dharmanlingam; Venkata, Murthy (Investigación Clínica, 2015)
The aim of the present research was to prepare and evaluate a gastroretentive drug delivery system for metformin HCl, using synthetic and semi-synthetic polymers. The floating approach was applied for preparing gastroretentive tablets (GRT) and these tablets were manufactured by the direct compression method. The drug delivery system comprises of synthetic and semi-synthetic polymers such as polyethylene oxide and Carboxymethyl ethyl cellulose (CMEC) as release-retarding polymers. GRT were evaluated for physico-chemical properties like weight variation, hardness, assay friability, in vitro floating behaviour, swelling studies, in vitro dissolution studies and rate order kinetics. Based upon the drug release and floating properties, two formulations (MP04 & MC03) were selected as optimized formulations. The optimized formulations MP04 and MC03 followed zero order rate kinetics, with non-Fickian diffusion and first order rate kinetics with erosion mechanism, re spectively. The optimized formulation was characterised with FTIR studies and it was observed that there was no interaction between the drug and polymers.